2022
DOI: 10.1037/apl0000992
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of perceiving organization members as a unified entity: Stronger attraction, but greater blame for member transgressions.

Abstract: Consequences of perceiving organization members as a unified entity: Stronger attraction, but greater blame for member transgressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
(209 reference statements)
0
3
0
Order By: Relevance
“…The relationships among our explanatory variables and our dependent variables may not have involved causality as we statistically analyzed explanatory variables (as per A. Chen & Treviño, 2022; Effron et al, 2022). Further, our sample sizes were generally moderate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships among our explanatory variables and our dependent variables may not have involved causality as we statistically analyzed explanatory variables (as per A. Chen & Treviño, 2022; Effron et al, 2022). Further, our sample sizes were generally moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Negative online information about that firm decreased participant attitudes toward the firm and lowered intention to buy from the firm. Another study found that negative user evaluations posted online (about a fictitious beverage company) had much stronger effects on the brand of the company than positive evaluations (Eberle et al, 2013).…”
Section: Political Doxingmentioning
confidence: 99%
“…After reading each job posting, participants rated the organization on its perceived trustworthiness (morality) by indicating the extent to which the terms trustworthy , honest , sincere , and ethical (α = .94; Effron et al, 2022; Leach et al, 2007) described that company on 5-point scales where 1 = not at all and 5 = extremely . In order to mask the research question, participants also rated items assessing the other two fundamental evaluative dimensions of warmth and competence (Leach et al, 2007) but only perceived trustworthiness effects were hypothesized.…”
Section: Methodsmentioning
confidence: 99%